INTEGRASI DISCOVERY LEARNING DALAM LKPD BERBASIS ETNOMATEMATIKA: UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI MOTIVASI BELAJAR - Nafisa Az'zahra; Muhamad Toyib (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2026)
In the context of junior high school mathematics learning, which is often perceived as unengaging by students, this study examines the effectiveness of student worksheets (LKPD) based on a discovery learning approach and ethnomathematics on students' mathematical problem-solving abilities, taking into account learning motivation and the interaction between the worksheets and that motivation. The research approach adopted was a quasi-experimental design with cluster random sampling, involving 55 ninth-grade junior high school students as research subjects, focusing on the topic of geometric transformations. Data were collected through tests and questionnaires. The test consisted of three essay items designed to measure mathematical problem-solving ability based on Polya's indicators. The findings reveal a significant effect of the Discovery Learning LKPD integrated with ethnomathematics, with a mean score of 84.39, compared to the Discovery Learning LKPD without ethnomathematics, which yielded a mean score of 75.44. Students with high learning motivation demonstrated stronger problem-solving abilities and were more effective at solving problems. Students with moderate learning motivation exhibited a mid-level ability, whereas those with low learning motivation tended to show lower performance. Therefore, the use of differentiated learning worksheets based on discovery learning integrated with ethnomathematics, alongside students' learning motivation, plays a supportive role in developing students' mathematical problem-solving abilities